Influence of Surfactants Solutions on Staphylococci Biofilm - Omar Abdulkareem Ali (Journal of Global Pharma Technology, 2016)
Staphylococci known to form biofilm on various clinical and biomaterials, so increase resistance to antimicrobial agents through biofilm formation strategy. The intracellular adhesion had been required for biofilm formation by Staphylococci. In this research, the main goal was detecting the biofilm formation capability regarding Staphylococcus sp. isolates on 96-well microtiter plates, also studying the impact of surfactants solutions extracted from Lactobacillus acidophilus in biofilm formed through Staphylococcus sp. Seventy-four Staphylococci isolates had be utilized in this research, the solid biofilm forming capacity had be confirmed through incubating these isolates in microtiter plates for 48 hours and at a temperature of 37Celsius. Afterward, during the next 24-48 hours, observations have made over removing the established biofilms of Staphylococci isolates with surfactants solution. The results hinted at the elimination of these biofilms in surfactants concentration-dependent way, with an observation that after 48 hours of incubation, the biofilm biomass reduction had been considerably greater.Keywords: Lactobacillus; Surfactants; Biofilm; Adhesion; Staphylococci.